Activating the expression of bacterial cryptic genes by rpoB mutations in RNA polymerase or by rare earth elements. (1st February 2014) - Ochi, Kozo; Tanaka, Yukinori; Tojo, Shigeo
Abstract: Since bacteria were found to contain genes encoding enzymes that synthesize a plethora of potential secondary metabolites, interest has grown in the activation of these cryptic pathways. Homologous and heterologous expression of these cryptic secondary metabolite-biosynthetic genes, often "silent" under ordinary laboratory fermentation conditions, may lead to the discovery of novel secondary metabolites. We review current progress on this topic, describing concepts for activating silent genes. We especially focus on genetic manipulation of transcription and translation, as well as the utilization of rare earth elements as a novel method to activate the silent genes. The possible roles of silent genes in bacterial physiology are also discussed.